A preliminary study of the chemical composition and bioactivity of Bombax ceiba L. flower and its potential mechanism in treating type 2 diabetes mellitus using ultra-performance liquid chromatography quadrupole-time-flight mass spectrometry and network pharmacology analysis - Yin, Kehong; Yang, Jinmei; Wang, Fang; Wang, Zhenxing; Xiang, Ping; Xie, Xing; Sun, Jian; He, Xuemei; Zhang, Xuechun (Frontiers in Nutrition, 2022)
This study aimed to preliminary investigate the phytochemistry, bioactivity, hypoglycemic potential, and mechanism of action of Bombax ceiba L. flower (BCF), a wild edible and food plant in China. By using methanol extraction and liquid-liquid extraction, the crude extract (CE) of BCF and its petroleum ether (PE), dichloromethane (DCM), ethyl acetate (EtOAc), n-butanol (n-BuOH), and aqueous (AQ) fractions were obtained, and their chemical components and biological activities were evaluated. Further high-performance liquid chromatography (HPLC) analysis was carried out to identify and quantify the active constituents of BFC and its five fractions, and the phytochemical composition of the best-performing fraction was then analyzed by ultra-performance liquid chromatography quadrupole-time-flight mass spectrometry (UPLC/Q-TOF-MS). Finally, a network pharmacology strategy based on the chemical profile of this fraction was applied to speculate its main hypoglycemic mechanism. Results revealed the excellent biological activities of BCF, especially the EtOAc fraction. In addition to the highest total flavonoid content (TFC) (367.72 μg RE/mg E) and total phenolics content (TPC) (47.97 μg GAE/mg E), EtOAc showed the strongest DPPH⋅ scavenging ability (IC50 value = 29.56 μg/mL), ABTS⋅+ scavenging ability (IC50 value = 84.60 μg/mL), and ferric reducing antioxidant power (FRAP) (889.62 μg FeSO4/mg E), which were stronger than the positive control BHT. EtOAc also exhibited the second-best α-glucosidase inhibitory capacity and second-best acetylcholinesterase (AChE) inhibitory capacity with the IC50 values of 2.85 and 3.27 mg/mL, respectively. Also, EtOAc inhibited HepG2, MCF-7, Raw264.7, and A549 cell with IC50 values of 1.08, 1.62, 0.77, and 0.87 mg/mL, which were the second or third strongest in all fractions. Additionally, HPLC analysis revealed significant differences in the compounds’ abundance between different fractions. Among them, EtOAc had the most detected compounds and the highest content. According to the results of UPLC/Q-TOF-MS, 38 compounds were identified in EtOAc, including 24 phenolic acids and 6 flavonoids. Network pharmacological analysis further confirmed 41 potential targets of EtOAc in the treatment of type 2 diabetes, and intracellular receptor signaling pathways, unsaturated fatty acid, and DNA transcription pathways were the most possible mechanisms. These findings suggested that BCF was worthwhile to be developed as an antioxidant and anti-diabetic food/drug.